Luka Tusuk di Pangkal Leher Menembus Paru-Paru Kanan yang Menyebabkan Kematian: Laporan Kasus Patologi Forensik - Hendri Meirialdi; Fahmi Irsan Nasution; Indah Afriwanty Simatupang (PPNI UNIMMAN, 2025)
Wound is the breakdown of tissue units/components, where specifically there are damaged or missing tissue substances. Several articles have their own definition of injury, based on the damage caused. This includes damage to internal organs. Another article also mentions the degree of injury, not based on its shape but based on the consequences that can endanger the life of the victim.A stab wound is a wound with a depth that exceeds the length of the wound due to a sharp-edged or blunt-edged tool that occurs with a perpendicular or oblique pressure on the body surface.In this case report, a male corpse was identified. From the results of the examination, the victim suffered several injuries due to sharp violence on the right forehead, left lower jaw, left shoulder, left upper arm, and right chest base of the neck, which tore the carotid artery and penetrated the right lung. so that the right lung ruptures and the presence of blood fluid in the chest cavity is as much as 2000 cc. The victim's death was caused by a stab wound at the base of the neck that hit the carotid artery and penetrated the right lung, causing bleeding, which resulted in suffocation.